Pendidikan Karakter Peserta Didik Kelas 6 SDN Purut Sebagai Pedagogik: Tinjauan Epistemologi Dan Aksiologi - Tri, Neneng; Silalahi, Suandi (Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to investigate and enhance character development practices among Grade 6 students at SDN Purut using an inquiry-based pedagogical approach grounded in epistemology and axiology. Employing Classroom Action Research (PTK) with a qualitative framework, the research unfolded in four phases: planning, action implementation, observation, and reflection. During the planning phase, a character education program was crafted to align with students' needs and pertinent values informed by the nature of knowledge and value theory regarding the significance and utility of education. The implementation phase focused on applying learning strategies designed to integrate character values such as discipline, responsibility, and empathy into everyday learning experiences. Data collection involved observation, in-depth interviews, and activity notes, which were subsequently analyzed through qualitative descriptive methods. The findings indicated that character education programs rooted in epistemology and axiology can enhance students' comprehension of character values while promoting constructive behavioral shifts within the school setting. This study adds to the advancement of value-centered teaching methods that can be utilized to enhance character education in primary schools.